2021
DOI: 10.3390/su13169097
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Role of Satisfaction with Life in the Effect of Self-Esteem and Education on Social Media Addiction in Turkey

Abstract: The increasing use of social media due to various individual and social reasons may trigger some psycho-social issues. What can be effective in reducing social media addiction, which causes social and economic problems, is an important issue today. This study aimed to investigate the mediation effect of satisfaction with life in the impact of self-esteem and education level on social media addiction in individuals. The study was designed as cross-sectional, and the sample consists of 952 volunteers over the ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
0
8
0
1
Order By: Relevance
“…However, no significant relationship was found in the sample in the same study, with no upper age limit obtained on the internet [111]. There are studies in the literature that find that satisfaction with life increases as age advances [112,113].…”
Section: Age and Family Type As Moderatorsmentioning
confidence: 61%
“…However, no significant relationship was found in the sample in the same study, with no upper age limit obtained on the internet [111]. There are studies in the literature that find that satisfaction with life increases as age advances [112,113].…”
Section: Age and Family Type As Moderatorsmentioning
confidence: 61%
“…These activities are likely to enhance consumer’s rights and increase customer’s satisfaction ( Sahibzada et al, 2020 ). A customer who makes an online transaction will be highly satisfied with a website that provides a great experience ( Koçak et al, 2021 ). Enhancing customer’s satisfaction, encouraging customer intentions, creating community loyalty, and fostering communication and interactions between community users are crucial to lasting community platform management ( Pang, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies have demonstrated acceptable psychometric properties of this scale in different cultural contexts (Andreassen et al, 2016;Bányai et al, 2017;Lin et al, 2017;Monacis et al, 2017). Psychometric analyses of the BSMAS in Turkish samples were shown to be satisfactory (Arslan et al, 2021;Demirci, 2019;Koçak et al, 2021). The internal consistency of BSMAS was 0.82 in the current sample.…”
Section: Happiness Scalementioning
confidence: 60%